JNC VI - Ray W. Gifford (Southern Medical Journal, 1997)
We present nationally representative estimates of cancer diagnoses among US persons with HIV (PWH) using data from the Medical Monitoring Project, a complex sample survey of US adults with diagnosed HIV. Data were collected June 2019-May 2023 from a probability sample of 14,798 PWH. Weighted frequencies and percentages of cancer diagnoses during the past 24 months were calculated, and differences between the groups were quantified using prevalence ratios. An estimated 66,641 PWH (6.7%) had a cancer diagnosis and 54,863 (5.5%) had a non-AIDS-defining cancer diagnosis. PWH with a cancer diagnosis had higher prevalence of formerly smoking cigarettes, being unable to work or retired, poor self-rated health, advanced HIV disease, retention in HIV care, and viral suppression compared with those without a cancer diagnosis. Providing recommended cancer screenings and cancer prevention and treatment strategies-in addition to HIV standard of care-may support overall well-being among PWH.